Applying an equity lens to urban policy measures for COVID-19 in four cities. (21st July 2021) - Cave, Ben; Kim, Jinhee; Viliani, Francesca; Harris, Patrick
ABSTRACT: This contribution focusses on equity and COVID-19 by comparing the urban responses in four cities: Sydney, Milan, Seoul and London. Key features of urban life, such as connectivity and interaction, accelerate the spread of COVID-19. We show some dimensions of urban health responses to minimise the spread of the 2019 novel coronavirus (SARS-CoV-2) in the population and how in this early phase cities have mainly implemented national policies. We look at sociospatial relations, including scale, and equity in cities and at the way the pandemic is reinforcing existing, and creating new, inequities. The proactive and empowered input from cities is critical as we simultaneously prepare for recovery and for subsequent waves of infection.